Improving warehouse efficiency of sparepart storage through comparison of dedicated and class-based storage methods - Prayoga Prima Hermawan; Qurtubi Qurtubi (Institute of Advanced Engineering and Science, 2026)
Warehouses play a crucial role in supporting the efficiency of supply chain operations, especially in material management and goods movement. However, in a company engaged in the paper printing and recycling industry, inefficiency in searching and retrieving goods in the spare parts warehouse is a major challenge, with a sub-optimal layout hampering smooth operations. This research offers a new perspective by evaluating the effectiveness of two storage methods, namely class-based storage and dedicated storage, in the context of spare parts warehouses that have different layout characteristics. This study aims to compare the two methods in improving material-handling efficiency and optimizing warehouse layout. The results show that the class-based storage method is more effective in reducing travel distance and material-handling time than dedicated storage. In addition, this method can improve operational efficiency and support the smooth production process through the arrangement of goods based on picking frequency. The theoretical implications of this research contribute to the development of warehousing management literature, while practically, the results of this study can serve as a guide for industries in implementing more efficient warehouse layout strategies.